Obtención y caracterización de suero de leche en polvo a partir de lactosuero de la empresa (PROLAD´S) mediante el método de secado por aspersión (spray dryer) - Loachamin Guallichico, Brandon Ernesto (2021)
The research project was carried out in order to optimize the process of obtaining and characterizing of powdered milk whey, therefore, the serum samples were collected to later carry out the analyzes. The runs were established using the Design Expert 8.0.6 program in which 11 runs were determined with different study factors such as air inlet temperature (170 ° C, 175 ° C and 180 ° C) and maltodextrin concentration (25%, 50%, and 75%). Whey is a by-product with great potential that has several nutrients. The physical-chemical analysis carried out on whey, lactose, milk protein, lactic fat, ash, titratable acidity, and pH stands out. In order to obtain the powdered whey, the whey sample was subjected to the Spray Dryer to determine the humidity and the total solids yield of the different experimental runs under the established conditions. The numerical optimization process of obtaining powdered whey was verified, by comparing the experimental values of humidity (3,22%) and total solids yield (91,23%), with those obtained from the optimization moisture (2,5%) and total solids yield (92,5%). The values obtained through experimentation in the case of humidity resulted in a higher value than the numerical optimization and the case of the total solids yield, the experimental value was higher than the numerical optimization.